Genetic characterization of emergent GII.17 norovirus variants from 2013 to 2015 in Nanjing, China. Issue 11 (16th November 2016) - Wang, Xuan; Du, Xuefei; Yong, Wei; Qiao, Mengkai; He, Min; Shi, Limin; Guo, Baofu; Hong, Lei; Jiang, Yun; Xie, Guoxiang; Ding, Jie
Abstract : N/A: During the 2014/15 winter season, a newly emergent GII.P17‐GII.17 variant overwhelmed currently dominant GII.4 viruses, causing outbreaks of acute gastroenteritis in China and Japan. In Nanjing area, this novel GII.17 variant was first identified in a sporadic case of acute gastroenteritis in July 2013, 18 months ahead of reports from other parts of China. In this study, epidemiological features and genotyping of noroviruses from 2013 to 2015 were depicted. Twenty‐eight local GII.17 sequences of capsid N‐terminus originating from July 2013 to August 2015 were aligned, among which complete genome of seven strains obtained from two outbreaks and five sporadic cases was extensively characterized. The differences of local GII.17 variants led to at least two clusters, with strains from 2013/14 season and those from 2014/15 season grouped differently. Multiple nucleotide and amino acid variations between different clusters of GII.17 were elucidated, including residue substitutions and insertion occurring in or near antigenic and receptor‐binding sites of viral protein 1. In addition, sequence hypervariability from residue 279 through 406 of viral protein 2 was identified. The modifications may reveal a distinctive adaptive process which could in part explain the rapid spread of emerging GII.17 variants. Continued monitoring on novel GII.17 is essential.